Integrated 6C Skills of the 21st Century with Animation Video Media for Arabic Speaking Material Design - Sarip, Mohamad; Ilham, Andri; Bahtiar, Ihwan Rahman; Hendrawanto, Hendrawanto; Laseduw, Siti Marwah Islami; Abdullah, Mukhtar (LPPM Universitas Pendidikan Mandalika, 2024)
This research aims to design a model of animated video-based Arabic language teaching materials that are integrated with 6C skills to face challenges in the 21st-century era. This research used a mixed approach using the Research & Development method. This research used the Borg and Gall model as an analysis procedure. This research was carried out in the 2022-2023 academic year at the Arabic Language Education Study Program at Jakarta State University. The participants were teachers, experts (Arabic language materials, curriculum), and students. Data collection techniques used observation, questionnaires, documents, interviews, and tests. Data analysis techniques used qualitative data from assessment experts and peer reviewers. Data was presented through statistical descriptions using percentages and means. The quantitative data was taken from the test result in the model's large trial test to determine the product's worthiness. It was done to determine the student's achievement in Arabic speaking skills. It used the t-test. The research results showed that students need classroom teaching materials to learn to speak Arabic, which involves the development of digital technology, namely animated videos. The topics used in the Arabic-speaking teaching material model were related to the achievement of 6C skills, which are relevant to character education values and appear in learning instructions. The content of teaching materials was also combined with reading skills as a source of information for students in carrying out speaking practice in class. Various forms of speaking practice refer to the concept of an oral test. Meanwhile, the use of animated videos is in the instructions for carrying out exercises so that students can use the videos as a reference for speaking practice. These findings also provided an understanding of the demands for the quality of educators' digital competence in designing class materials.